International Multispecialty Consensus on How to Evaluate Ultrasound Competence: A Delphi Consensus Survey - Tolsgaard, Martin G. (Public Library of Science, 2013)
OBJECTIVES: To achieve international consensus across multiple specialties on a generic ultrasound rating scale using a Delphi technique. METHODS: Ultrasound experts from Obstetrics-Gynaecology, Surgery, Urology, Radiology, Rheumatology, Emergency Medicine, and Gastro-Enterology representing North America, Australia, and Europe were identified. A multi-round survey was conducted to obtain consensus between these experts. Of 60 invited experts, 44 experts agreed to participate in the first Delphi round, 41 remained in the second round, and 37 completed the third Delphi round. Seven key elements of the ultrasound examination were identified from existing literature and recommendations from international ultrasound societies. All experts rated the importance of these seven elements on a five-point Likert scale in the first round and suggested potential new elements for the assessment of ultrasound skills. In the second round, the experts re-rated all elements and a third round was conducted to allow final comments. Agreement on which elements to include in the final rating scale was pre-defined as more than 80% of the experts rating an element four or five, on importance to the ultrasound examination. RESULTS: Two additional elements were suggested by more than 10% of the experts in the first Delphi round. Consensus was obtained to include these two new elements along with five of the original elements in the final assessment instrument: 1) Indication for the examination 2) Applied knowledge of ultrasound equipment 3) Image optimization 4) Systematic examination 5) Interpretation of images 6) Documentation of examination and 7) Medical decision making. CONCLUSION: International multispecialty consensus was achieved on the content of a generic ultrasound rating scale. This is the first step to ensure valid assessment of clinicians in different medical specialties using ultrasound.